2000
DOI: 10.1046/j.1365-2044.2000.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Closed loop control of anaesthesia: an assessment of the bispectral index as the target of control

Abstract: SummaryWe investigated the performance of a closed-loop system for administration of general anaesthesia, using the bispectral index as a target for control. One hundred patients undergoing gynaecological or general surgery were studied. In 60 patients, anaesthesia was maintained by intravenous infusion of a propofol/alfentanil mixture. In 40, an isoflurane/nitrous oxide based technique was used. For each technique, patients were randomly allocated to receive either closed-loop or manually controlled administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 17 publications
1
55
0
3
Order By: Relevance
“…7 Previous studies have shown that the BIS is well suited as a control variable for closed-loop systems. 1,2,[8][9][10][11] Also, studies have shown that closed-loop systems using the BIS outperform manual control. 3,5,6 Relying on a single input signal, the controller can be misled by artefacts that can occur on the EEG signals, and this poses an inherent safety risk to the patient.…”
Section: Résumémentioning
confidence: 99%
“…7 Previous studies have shown that the BIS is well suited as a control variable for closed-loop systems. 1,2,[8][9][10][11] Also, studies have shown that closed-loop systems using the BIS outperform manual control. 3,5,6 Relying on a single input signal, the controller can be misled by artefacts that can occur on the EEG signals, and this poses an inherent safety risk to the patient.…”
Section: Résumémentioning
confidence: 99%
“…A closed-loop controller was described with the BIS Monitor and a fixed mixture of propofol and alfentanil. 7 Use of an isoboller controller has also been de- Data are presented as median ͓interquartile range͔ or number (%) of total patients of each group. Time to tracheal extubation was defined as the time from discontinuation of propofol and remifentanil infusion until tracheal extubation.…”
Section: Discussionmentioning
confidence: 99%
“…The Bispectral index (BIS) is a single composite measure derived from the spontaneous EEG and has been proven to have a high sensitivity and specificity to measure anaesthetic drug effect (Morley et al, 2000;Struys et al, 2003). BIS is now recognized as one of the reference measures of DOA for closed loop control purposes (Ionescu et al, 2008;Absalom et al 2011;Liu et al, 2011).…”
Section: The Multivariable Paradigm Of Automated Doamentioning
confidence: 99%
“…Analgesics block the sensation of pain; the hypnotics produce unconsciousness, while the muscle relaxants prevent unwanted movement of muscle tone. The relationship between the hypnotic drug, Propofol, administered during general anaesthesia, and BIS (a signal derived from the electroencephalogram used to assess the level of consciousness during anaesthesia) is widely documented and several studies regarding the interaction model of Propofol and Remifentanil can be found in the literature (Morley et al, 2000;Struys et al, 2003;Absalom et al, 2011). When inducing and maintaining anaesthesia, anaesthesiologists select initial doses based on a variety of considerations, they observe the results, and then make adjustments based on several factors, at irregularly varying intervals.…”
Section: Introductionmentioning
confidence: 99%